2021
DOI: 10.25259/ijms_94_2021
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress among doctors working in a dedicated COVID-19 hospital in North India

Abstract: Objectives: The present study was aimed to assess the level of perceived stress among doctors working in COVID-19 ward in a tertiary care medical college and hospital of North India and to find the association of stress with time spent in ward, age, and designation of the doctors. Material and Methods: It was a cross-sectional, Google-based survey conducted in October and November 2020. The form was circulated and recorded the sociodemographic data, time spent in the COVID-19 ward, etc. The perceived stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…However, young healthcare professionals and those working in clinical departments have higher stress levels, anxiety, and depression than their senior coworkers and those in non-clinical departments [31,35]. Conversely, there was a positive correlation obtained between the designation of HCWs and their coping behavior in the present study.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…However, young healthcare professionals and those working in clinical departments have higher stress levels, anxiety, and depression than their senior coworkers and those in non-clinical departments [31,35]. Conversely, there was a positive correlation obtained between the designation of HCWs and their coping behavior in the present study.…”
Section: Discussioncontrasting
confidence: 70%
“…Similarly, the uncertainty and last-minute work schedules severely impacted the daily lives of those working in Denmark's hospitals [33]. Another indirect consequence is HCWs' weariness in the form of tiredness and irritability [34,35]. Those working in Iran experienced similar physical tiredness, as well as skin damage and hormonal imbalance [32].…”
Section: Discussionmentioning
confidence: 99%
“…At the personal level, up to half of the participants said that they felt emotional tiredness or burnout; this was also reported by hospital managers in Pakistan [ 6 ]. This study suggests that increased challenges for HCWs in their personal life may result from an increased workload at the workplace, the designation of HCWs, their living status, the distance of green spaces from their home, and the frequency with which they visit green spaces for recreational activities [ 9 ]. Incompetence at work, the fear of contracting a COVID-19 infection, ethical dilemmas, sleep-related problems, and a difficulty in communicating their problems to others were commonly reported challenges faced by the participants, similar to previous studies across countries [ 6 , 7 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Feeling confined, having difficulty breathing, and experiencing frustration were some of the challenges reported by Indian nurses after wearing personal protective equipment (PPE) kits at work [ 8 ]. Doctors posted in a COVID-19-dedicated ward at an Indian tertiary hospital very often felt nervous, upset, and were unable to cope with the COVID-19 situation [ 9 ]. Studies reported severe to moderate levels of anxiety among Indian HCWs in 2020 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study, doctors noted that a lot of their stress comes from how they don't have adequate time with their loved ones. 2 They experienced work burnout. With the already existing shortage of doctors and healthcare workers in India, newly licensed physicians may be concerned about burnout.…”
Section: Prior Researchmentioning
confidence: 99%